Developing a Culture of Continuous Learning for Sustainable Job Performance: TEVT Sector as Learning Organization, Pakistan. (Journal of Social Sciences Review, 2023)
This study explores the role of Technical Support (TS) and Leadership Support (LS) in enhancing Employee Performance (EP) through the development of a Culture of Continuous Learning (CCL) in the Technical Education and Vocational Training (TEVT) sector of southern Punjab. Data from 291 TEVT trainers were analyzed using Smart PLS4. The results show that TS and LS have a positive impact on CCL, leading to improved EP. Employee Engagement (EE) moderates these effects, revealing barriers such as overwhelmed employees, limited relevance of learning programs, and a perceived lack of support and recognition. To overcome these challenges, organizations can provide support structures like mentoring and coaching. These findings emphasize the importance of TS, LS, and CCL in enhancing EP in the TEVT sector and suggest further research to explore additional factors for improved employee performance in resource-constrained environments.
Keywords: Technical Support; Leadership Support; Culture of Continuous Learning; Employee Engagement; Employee Performance